KINERJA BADAN NARKOTIKA KABUPATEN DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOBA DI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Rezky Putra Ramadhan Rezky Ramadhan (JIA: Jurnal Ilmiah Administrasi, 2020)
The purpose of this study was to determine the performance of the District Narcotics Agency (BNK) in Drug Abuse Management in the Panca Rijang District of Sidenreng Rappang Regency and the factors that influenced the Performance of the Narcotics Agency (BNK) in drug abuse prevention in Panca Rijang Sub-District, Sidenreng Rappang District. The population is 26,149 people in Panca Rijang Subdistrict aged 18 years and above. The sample in this study was 100 people in the District of Panca Rijang, based on purposive sampling techniques or determination of samples with certain criteria with sampling techniques using Slovin formula.. This type of research is quantitative descriptive with basic research, survey research with descriptive explanatory level, and the type of data in this study is quantitative research.The results of the Performance of the District Narcotics Agency (BNK) in the prevention of drug abuse in the Panca Rijang District of Sidenreng Rappang Regency are in the "less good" category with a percentage of 55%. As for the factors that influence the Performance of the District Narcotics Agency (BNK) in drug abuse prevention in Panca Rijang Subdistrict, Sidenreng Rappang Regency, the first factor has a percentage of 63% with the category "Enough effect", the second factor has a percentage of 62.6% with the category "Fairly influential", and the third factor has a percentage of 60.6% with the category "Poor", based on the results of the average recapitulation of the percentage of factors that affect BNK performance in overcoming drug abuse as much as 62%, and are in the "Enough Effect" category. Keywords:Performance of the District Narcotics Agency The purpose of this study was to determine the performance of the District Narcotics Agency (BNK) in Drug Abuse Management in the Panca Rijang District of Sidenreng Rappang Regency and the factors that influenced the Performance of the Narcotics Agency (BNK) in drug abuse prevention in Panca Rijang Sub-District, Sidenreng Rappang District. The population is 26,149 people in Panca Rijang Subdistrict aged 18 years and above. The sample in this study was 100 people in the District of Panca Rijang, based on purposive sampling techniques or determination of samples with certain criteria with sampling techniques using Slovin formula.. This type of research is quantitative descriptive with basic research, survey research with descriptive explanatory level, and the type of data in this study is quantitative research.The results of the Performance of the District Narcotics Agency (BNK) in the prevention of drug abuse in the Panca Rijang District of Sidenreng Rappang Regency are in the "less good" category with a percentage of 55%. As for the factors that influence the Performance of the District Narcotics Agency (BNK) in drug abuse prevention in Panca Rijang Subdistrict, Sidenreng Rappang Regency, the first factor has a percentage of 63% with the category "Enough effect", the second factor has a percentage of 62.6% with the category "Fairly influential", and the third factor has a percentage of 60.6% with the category "Poor", based on the results of the average recapitulation of the percentage of factors that affect BNK performance in overcoming drug abuse as much as 62%, and are in the "Enough Effect" category. Keywords:Performance of the District Narcotics Agency